2008
DOI: 10.1111/j.1365-2427.2007.01921.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface sediment diatom assemblages and epilimnetic total phosphorus in large, shallow lakes of the Yangtze floodplain: their relationships and implications for assessing long‐term eutrophication

Abstract: 1. The Yangtze floodplain (SE China) is characterized by a number of large shallow lakes, many of which have undergone eutrophication due to the intensification of agriculture and urban growth over recent decades. As monitoring data are limited and in order to determine lake baseline nutrient concentrations, 49 lakes were sampled, covering a total phosphorus (TP) gradient (c. 30-550 lg L )1 ) to develop a diatom-based inference model. 2. There are three dominant diatom assemblages in these shallow lakes with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(126 citation statements)
references
References 57 publications
8
117
0
1
Order By: Relevance
“…It was obvious that the historical trophic status of the lakes along the middleÀlower reaches of the Yangtze River were already at an intermediate-eutrophic level at the beginning of the 200-yr period, which was in accordance with diatom-inferred TP studies in the same region (Yang et al 2008). Theoretically, the reasons for high background concentrations of nutrients are related to their morphological characteristics.…”
Section: Regional Characteristics Of Long-term Lake Nutrient Variationssupporting
confidence: 61%
See 1 more Smart Citation
“…It was obvious that the historical trophic status of the lakes along the middleÀlower reaches of the Yangtze River were already at an intermediate-eutrophic level at the beginning of the 200-yr period, which was in accordance with diatom-inferred TP studies in the same region (Yang et al 2008). Theoretically, the reasons for high background concentrations of nutrients are related to their morphological characteristics.…”
Section: Regional Characteristics Of Long-term Lake Nutrient Variationssupporting
confidence: 61%
“…By the end of the twentieth century, most of the lakes in the middleÀlower reaches of the Yangtze River had degraded to mesotrophic or eutrophic status (Qin 2002;Yang et al 2008). Much research has been conducted on lake eutrophication in different regions (Perrow & Davy 2002;Qin 2002;Phillips et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, for the past 50 a, the continuously deteriorating eutrophication has been unprecedented, possibly due to the retention of water in response to increasing occurrences of blocked river systems (by man-made dams and water reclamation), as well as the reduced self-purification abilities of lakes as a result of prolonged residence times of nutrients. Indeed, a study of nutrient changes in Lake Longgan on centennial scales revealed that climatic changes serve as the main reason for changes in the nutrients before 1950, after which human activities played a key role, accounting for 60% and 57% of the total TP variations in sediment and in lake water, respectively [98].…”
Section: Centennial Scalesmentioning
confidence: 99%
“…To emphasize the impact of human activities on the response of diatom assemblages in surface sediments to water levels, the diatoms of summer samples were identified since supplementary water flowed into the lake from the reservoir in the upper reach between spring and summer. Ordination methods were used to determine the effect of environmental factors on sedimentary diatom distribution (Yang et al, 2008). Detrended correspondence analysis (DCA) was used to estimate the gradient length of the first axis of the diatom distribution.…”
Section: Response Of Diatom Assemblages To Environmental Variablesmentioning
confidence: 99%